2011
DOI: 10.1111/j.1743-6109.2011.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Option for the Correction of Peyronie's Disease: An Autologous Tissue-Engineered Endothelialized Graft

Abstract: Introduction Surgical treatment is indicated in severe cases of Peyronie's disease. Incision of the plaque with subsequent graft material implantation is the option of choice. Ideal graft tissue is not yet available. Aim To evaluate the use of an autologous tissue-engineered endothelialized graft by the self-assembly method, for tunica albuginea (TA) reconstruction in Peyronie's disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…47 Tissue engineered graft materials such as adipose tissue-derived stem cell seeded SIS, human acellular matrix tunica albuginea grafts, and autologous tissue engineered endothelialized tunica albuginea grafts are being investigated for incision/excision procedures. [68][69][70][71] Imbeault et al 71 demonstrated in vitro creation of artificial tunica albuginea using human dermal fibroblasts and human endothelial cells. They concluded that this tissue-engineered endothelialized tubular graft was structurally similar to normal tunic with a high burst pressure and adequate mechanical resistance.…”
Section: Tunical Lengthening Procedures (Incision or Partial Excisionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Tissue engineered graft materials such as adipose tissue-derived stem cell seeded SIS, human acellular matrix tunica albuginea grafts, and autologous tissue engineered endothelialized tunica albuginea grafts are being investigated for incision/excision procedures. [68][69][70][71] Imbeault et al 71 demonstrated in vitro creation of artificial tunica albuginea using human dermal fibroblasts and human endothelial cells. They concluded that this tissue-engineered endothelialized tubular graft was structurally similar to normal tunic with a high burst pressure and adequate mechanical resistance.…”
Section: Tunical Lengthening Procedures (Incision or Partial Excisionmentioning
confidence: 99%
“…Furthermore, the autologous property of this model could represent an advantage comparatively to other available grafts. 71 Such studies may help elucidate future surgical treatments for PD using tissue engineered grafts for reconstruction of the tunica albuginea. The biomechanical properties, compatibility with tunica albuginea, and the effective neovascularization of the tissue engineered grafts need to be investigated further before such basic research can be applied by the reconstructive urologist.…”
Section: Tunical Lengthening Procedures (Incision or Partial Excisionmentioning
confidence: 99%
“…Mean penile girth was measured preoperatively and 6 months postoperatively in the flaccid and erect states; the mean penile girth had increased significantly after 6 months, and 94.2% of patients were satisfied with the procedure. In another study, 12 patients underwent repeated penile widening using biodegradable scaffolds enriched with expanded autologous scrotal dartos cells [96]; penile girth increased in both flaccid and erect states. Furthermore, 10-14 months after first surgery, biopsies showed highly vascularized loose tissue with collagen deposition and some inflammation, and after 22-24 months, biopsies revealed almost no inflammation and a tissue resembling normal dartos fascia.…”
Section: Penile Enhancementmentioning
confidence: 99%
“…Peyronie's disease is a benign, acquired wound-healingconnective-tissue disorder of the tunica albuginea that affects 3-9% of men [96]. Therapeutic options for Peyronie's disease include plication, incision and grafting, and penile prosthesis.…”
Section: Tunica Albuginea Repairmentioning
confidence: 99%
See 1 more Smart Citation